2001
DOI: 10.1667/0033-7587(2001)156[0251:poddan]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Production of Delayed Death and Neoplastic Transformation in CGL1 Cells by Radiation-Induced Bystander Effects

Abstract: Other investigators have demonstrated by transfer of medium from irradiated cells and by irradiation with low-fluence alpha particles or microbeams that cells do not have to be directly exposed to ionizing radiation to be detrimentally affected, i.e. bystander effects. In this study, we demonstrate by transfer of medium from X-irradiated human CGL1 hybrid cells that the killing of bystander cells reduces the plating efficiency of the nonirradiated CGL1 cells by 33 +/- 6%. In addition, we show that the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…These results suggested that irradiated cells secreted a cytotoxic factor into the culture medium, which was capable of killing nonirradiated cells. Furthermore, transferring media from low linear energy transfer-irradiated cultures to nonirradiated cells lead to increased levels of various bystander effects, such as cell killing (18)(19)(20), neoplastic transformation (21), and genomic instability (22). In contrast, in feeder layer culture, metabolic cooperation between cells of similar or different types increases the clonogenic survival of the nonirradiated cells by providing growth factors and matrix support and is considered a positive aspect of the bystander phenomenon.…”
mentioning
confidence: 99%
“…These results suggested that irradiated cells secreted a cytotoxic factor into the culture medium, which was capable of killing nonirradiated cells. Furthermore, transferring media from low linear energy transfer-irradiated cultures to nonirradiated cells lead to increased levels of various bystander effects, such as cell killing (18)(19)(20), neoplastic transformation (21), and genomic instability (22). In contrast, in feeder layer culture, metabolic cooperation between cells of similar or different types increases the clonogenic survival of the nonirradiated cells by providing growth factors and matrix support and is considered a positive aspect of the bystander phenomenon.…”
mentioning
confidence: 99%
“…Cytotoxic and clastogenic effects were detected on nonirradiated cells in contact with irradiated cells or exchanged via the culture medium (Hallahan et al, 1989;Mothersill and Seymour, 1997;Bishayee et al, 2001; Lewis et al, 2001;Sawant et al, 2002). The contribution of such bystander effects to radiation-induced cell death can be significant.…”
mentioning
confidence: 99%
“…Mothersill and Seymour (1997) first demonstrated a highly significant reduction in cloning efficiency in both non-irradiated normal as well as malignant epithelial cell lines that had received media from 60 Co-g-ray-irradiated human epithelial cell cultures. Further studies found that transferring media from low or high linear energy transfer-irradiated cultures to non-irradiated cells led to increased levels of various bystander effects, such as cell killing (Mothersill and Seymour, 1998;Lyng et al, 2000;Nagar et al, 2003), neoplastic transformation (Lewis et al, 2001), proliferation (Iyer and Lehnert, 2000) and genomic instability . These studies suggested that irradiated cells secreted a cytotoxic factor such as reactive oxygen species (ROS), transforming growth factor-b1 (TGF-b1) or interleukin-8 (IL-8 Nitric oxide as a signal in bystander effects W Han et al into the culture medium which was capable of causing damage in non-irradiated cells.…”
Section: Discussionmentioning
confidence: 99%